How the Local Wisdom Influences the Sustainability of Spatial Development in Denpasar, Bali, Indonesia - Dwijendra, Ngakan Ketut Acwin (BHUMI: Jurnal Agraria dan Pertanahan, 2021)
The urban development in Bali, especially Denpasar City, as the capital city of Bali Province, is growing fast in all sectors, leading to dynamic of city and creating some issues as well. Some aspects which have changed due to those developments are the growth of economics, the adequate of facilities and utilities, the comfort, the safety and the local wisdom of Balinese tradition as well. The local wisdom of Bali, as the cultural value system of Balinese tradition, is a solid reliability between culture and religion which becomes the root and the base of all Balinese community life. The existence of Balinese cultural value has been kept so far, it is not beyond the fundamental rules and meanings. In fact, the power of Balinese traditional sophistication value system is shaping the growth of Denpasar City. This article will explore the aspects of Balinese local wisdom values such as: Balinese traditional spatial pattern, traditional community and religion systems, also how those aspects have strongly generated the development of Denpasar city, especially on city spatial and land use. The study shows that existence of the local wisdom has significant factors in shaping urban patterns and structures and providing limitations to the use of urban space.